2015
DOI: 10.3390/ijerph120201054
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Tropical Cyclones and Accompanying Precipitation on Infectious Diarrhea in Cyclone Landing Areas of Zhejiang Province, China

Abstract: Background: Zhejiang Province, located in southeastern China, is frequently hit by tropical cyclones. This study quantified the associations between infectious diarrhea and the seven tropical cyclones that landed in Zhejiang from 2005–2011 to assess the impacts of the accompanying precipitation on the studied diseases. Method: A unidirectional case-crossover study design was used to evaluate the impacts of tropical storms and typhoons on infectious diarrhea. Principal component analysis (PCA) was applied to el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“…Typhoons mostly occur in southeast China and are much less researched on than floods, likely because of the relatively less significant human and economic loss. Research findings on typhoons are similar to those for floods, with association with infectious diarrhea found, 199 , 200 , 201 except for one study in Guangdong, 202 and with PTSD 203 , 204 . A study in Guangzhou found that typhoon could increase the all-cause mortality, particularly among female, very young and old population 205 .…”
Section: Climate Phenomenon (4): Extreme Weather Eventssupporting
confidence: 54%
“…Typhoons mostly occur in southeast China and are much less researched on than floods, likely because of the relatively less significant human and economic loss. Research findings on typhoons are similar to those for floods, with association with infectious diarrhea found, 199 , 200 , 201 except for one study in Guangdong, 202 and with PTSD 203 , 204 . A study in Guangzhou found that typhoon could increase the all-cause mortality, particularly among female, very young and old population 205 .…”
Section: Climate Phenomenon (4): Extreme Weather Eventssupporting
confidence: 54%
“…Within seven days, significant increases were seen in diarrhea or gastroenteritis in flooded households and in visits to treatment facilities 74 75 , 82 An analysis of national surveillance system data found an increased risk for shigellosis and other infectious diarrhea, peaking at five days post-cyclone (odds ratio [OR]: 3.56; 95% CI, 2.98-4.25) 83 . Within five weeks of landfall, the proportion of visits to treatment facilities for diarrhea remained significantly higher than pre-storm levels at an ECF, 80 the RR for visiting an ECF for diarrhea was elevated (RR: 2.0; 95% CI, 1.4-2.8) compared to a same week in the previous year, 79 and a community survey found a slightly higher risk of diarrhea in two of four storm-affected areas (Area 1 OR: 1.6; 95% CI, 1.52-1.65 and Area 2 OR: 1.3; 95% CI, 1.21-1.32) compared to the previous two years 84 .…”
Section: Resultsmentioning
confidence: 99%
“…In South Korea, during the typhoon periods in 2003, cases of infectious diarrhea hospitalization significantly increased [ 24 ]. A study in China manifested that typhoons and tropical storms increased the risk of bacillary dysentery and other infectious diarrhea in Zhejiang province [ 13 ]. Another study in Myanmar, showed that atypical increases in diarrheal disease and especially dysentery cases occurred in 2008 following Cyclone Nagis compared to 2007 and 2009 [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among evacuees of this typhoon, the number of acute gastroenteritis with diarrhea peaked on the seventh day after hurricane [ 26 ]. In Zhejiang province of China, the largest effect of typhoon and tropical storms was on lag 5 day and lag 6 day [ 13 ]. These studies had different delayed effects, which were biologically plausible because lag days were all within the incubation periods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation